Effects of social support on cognitive frailty among the older adults in China: mediation of psychological resilience and moderated mediation of education - Li, Wenjuan; Ma, Yiwen; Wei, Jinli; Wu, Shanzheng; Cui, Liangliang; Zhou, Chengchao (Frontiers in Aging Neuroscience, 2025)
ObjectivesPrevious research has revealed a relationship between social support and cognitive frailty. However, the underlying mechanisms of this connection have still not been well explored. The study aimed to investigate the effect of social support on cognitive frailty, mediated by psychological resilience and to examine the moderated mediation effect of education.MethodsA total of 1,758 older adults aged 60 years and above were included in the analysis. A descriptive analysis was conducted to describe the sample characteristics. The moderated mediation models were examined using Mplus 8.3, in which the mediation variables was psychological resilience, and the moderation variable was education.ResultsThe prevalence of cognitive frailty among the older adults was 4.3%. Social support had a significant negative predictive effect on the cognitive frailty (B = −0.066, p < 0.01), the psychological resilience partially mediated the relationship between social support and cognitive frailty (B = −0.103, p < 0.001). Compared to illiterate, primary school (B = −0.184, p < 0.05), middle school (B = −0.244, p < 0.01) and high school or above (B = −0.315, p < 0.01) could regulate the relationship between social support and psychological resilience in older adults.DiscussionWe present a conceptual model containing the mediated effects of psychological resilience and the moderated effect of education on the relationship between social support and cognitive frailty. We believe this model enhances understanding of these associations and could be instrumental in formulating intervention strategies to mitigate the incidence of cognitive frailty in older adults.